Respuesta :

Simplifying

2x + -1y + -3z = 5

Solving

2x + -1y + -3z = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.

2x + -1y + y + -3z = 5 + y

Combine like terms: -1y + y = 0

2x + 0 + -3z = 5 + y

2x + -3z = 5 + y

Add '3z' to each side of the equation.

2x + -3z + 3z = 5 + y + 3z

Combine like terms: -3z + 3z = 0

2x + 0 = 5 + y + 3z

2x = 5 + y + 3z

Divide each side by '2'.

x = 2.5 + 0.5y + 1.5z

Simplifying

x = 2.5 + 0.5y + 1.5z